THE TRANSFORMATIVE ROLE OF ENTREPRENEURSHIP AND ECONOMIC RELATIONS IN PUBLIC DIPLOMACY: ANALYSIS OF HISTORICAL EXPERIENCE AND CONTEMPORARY TRENDS - Alimardonov, Otabek Kudratovich (Oriental Journal of History, Politics and Law, 2025)
This article analyzes the interconnection between entrepreneurship and economic relations within the framework of public diplomacy, focusing on historical experiences and modern trends. Drawing on historical case studies and contemporary data, the author demonstrates the significant role of merchants and entrepreneurs in cultural, social, and political interactions across nations. Entrepreneurs are evaluated as key actors in public diplomacy. The study also highlights recent developments in paradiplomacy and sister city partnerships. Using Uzbekistan as a case study, the impact of national entrepreneurship and handicrafts on international cooperation and diplomacy is explored.